GENETIC CHARACTERIZATION OF GALOBA DURIAN (AMONUM SPP.) IN AMBON ISLAND BASED ON RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) - Fuadiska Salamena; Adriana Hiariej; Cecilia Anna Seumahu (Agrotech Journal, 2018)
Galoba durian is one of the endemic floras from Maluku. Galoba durian is a species belonging to the Amomum genera Zingiberaceae family. It is also used as a medicinal plant for waist and kidney diseases. Based on the color of the fruit, galoba durian is divided into two nmely red galoba durian and green galoba durian. Distribution of this plant in Ambon can found in a few places such as highland and coastal area. Different locations influence phenotypic of plants, but may not show different genetic characteristic. Genetic diversity can detected by molecular markers. Genetic characterization from galoba durian using RAPD markers has not been done before. This study aimed to analyze genetic diversity from galoba durian using molecular markers RAPD. Samples of plants are used red galoba durian from Hatu and green galoba durian from Hatalae. The result of the first study, characterization of the morphology of the galoba durian, showed that both galoba have almost similar characteristics. Further DNA was tested by qualitative and quantitative. Result shows good qualitative and quantitative of DNA genomic. The second study was amplification by PCR-RAPD. DNA amplifications were performed using 3 primers out of 9 screened random primers. The primers selection was based on hight polymorphism. DNA amplification has 36 bands which were 100% polymorphic. The size of each bands from visualization of agarose was determined by linear regression. Number of band amplified was range from 120 to 1612 bp. Polymorphic band of RAPD showed the highest  genetic diversity. It can be concluded that the two plants of galoba durian are different species